The effects of leg preference and leg dominance on static and dynamic balance performance in highly-trained tennis players. - Žiga Kozinc (Public Library of Science (PLoS), 2021)
In this study, 90 (51 males, 39 females) tennis players performed single-leg quiet stance and single-leg landing tasks. For the static standing task, center-of pressure (CoP) velocities, amplitudes, frequency and area were calculated. For the landing tasks, time to stabilization as well as dynamic postural stability index were considered. The analysis of differences between the legs was done based on two methods for a priori determination of leg preference, one based on the preference of kicking a ball and one based on the preference for single-leg jumping. An additional analysis was done based on the leg dominance (determined post hoc), based on the observed performance of the tasks. In case of the classification based on kicking a ball, there was a statistically significantly lower CoP anterior-posterior velocity and anterior-posterior amplitude in static balance task (p ≤ 0.017; 0.17 ≤ d ≤ 0.28) for the preferred leg. The CoP frequency was higher in the preferred leg for both directions (p ≤ 0.002; 0.10 ≤ d ≤ 0.22). For the landing task, CoP medial-lateral time to stabilization was statistically significantly shorter for the preferred leg (0.28 ± 0.38 s) compared to the non-preferred leg (0.47 ± 0.60 s) (p = 0.012; d = 0.38). There were no differences between the legs for the landing task. Moreover, there were no differences between the legs when we used the preference based on jumping for either of the tasks (d ≤ 0.14). The differences between legs in terms of observed dominance were larger than the differences based on the preference, which stresses the need for clear distinction of limb preference and limb dominance in research and practice. Regarding the effect of leg preference, small differences in static balance may exist between the legs (when the preference is based on kicking a ball).